Effect inclusion of graphene on the mechanical properties of polymer nanocomposites - Sairy, Nur Aqilah; Mazlan, Norkhairunnisa; Ishak, Mohamad Ridzwan; Zulkepli, Nik Noriman (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Graphene-based nanocomposites have introduced to the development of flexible nanocomposite as for emerging applications like as in need of superior of thermal, mechanical, electrical, chemical and optical performance. Sp2-hybridized carbon atoms are arranged in a two-dimensional lattice which is a monolayer that produces the graphene. Graphene has gained significantly as fillers in the nanocomposite due to it has various intriguing properties. This review will discuss the effect of inclusion of graphene on the mechanical properties of polymer nanocomposites.